A Total systems study of the Manila Buying Station Agribusiness Division San Miguel Corporation - Azarcon, Ma. Elaine C.; Dizon, Elizabeth Joyce J.; Fandino, Mary Roselet G.; Gimalay, Anna Liza Constance C.; Gonzales, Aimee Josephine P.; Lim, Ada Liesl Maria C.; Santos, Emalyn V.; Villanueva, Christine M. (College of Engineering, 1989)
The object of the system study is the Manila Buying Station (MBS)/Warehousing of the Fruits Business Unit, Agribusiness Division of the San Miguel Corporation. Its present charter is to receive and dispatch fruits for processing and for export. Currently, the MBS/Whse is under the Export Services Department whose function is to develop and service the requirements for processed and unprocessed products of the Magnolia Division and non-competitive food products of other companies that have strategic importance to the Corporation in the international as well as in some identified domestic markets. After an evaluation of the MBS/Whse and its relationship with other entities that they regularly interact with, three main problem areas were found. The first problem is the unreliability of the fruit supply. It is not uncommon for a fruit delivery from a supplier to reach MBS at a time and with a volume different than what was agreed upon. This brings about difficulties for the MBS and the Production Dept., which is in charge of processing the fruits. Another problem of the system is concerned with the functions of the MBS/Whse. After a study of the charter and the present procedure of the MBS/Whse personnel, it appears that the scope of the functions is unclear. The last problem is about the physical inventory of the fruits in the fruit processing plant that comes from the MBS. The volume of the fruits that are delivered does not tally with delivery records. This problem creates some hitches in the monitoring of the inventory levels. In the analysis of these problems, several alternative solutions were formulated. Then, these are assessed against a set of criteria in order to come up with a better system. All of the chosen alternatives are incorporated in the System Design, which is composed of the following elements: a) as an answer to the problem regarding the scope of functions of the MBS\Whse, a redefinition of the charger and a modification of the reporting system are called for. With this proposal the MBS activities are to be reported to the Materials department, and all the MBS/Whse activities to the ESD; b) a model for the Buying Process is formulated so as to determine the areas that the FES should concentrate their efforts on. Considering the levels of supply and demand, the model can specify when direct buying, contract farming, and incentive grants may be employed; c) Since the supplier is partly responsible for the problem of the unreliability of fruit supply, it is important to evaluate their performance. Hence, a model using the Multi-Attribute Utility Technology is devised to determine who the reliable suppliers are; d) to aid the workers in sorting the fruits, they may use a sackmat to reduce their movements. Pictures of the fruits may be posted to serve as reference. An arrangement of the sorters and the crates is recommended in the sorting of mangoes to reduce clutter and movement; e) Using historical data, the manpower requirements can be determined. In this study, the number of sorters and loaders for the guyabano season is computed; f) Work Measurement may be employed in the sorting process. This is to develop sorting standards which can be a guide for future rehiring of workers who can sort within the standard time and to determine the number of sorters needed per day and per fruit season.